2014
DOI: 10.1086/676869
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Algorithm for Electronic Surveillance of Hospital-Acquired Infections Yielding Serial Weekly Point Prevalence Scores

Abstract: Surveillance of hospital-acquired infections can be approximated by repeated surveys that are performed in a standardized, cost-effective manner. We developed an integrated software system for serial electronic hospital-wide point prevalence surveys using algorithms that proved highly sensitive and specific over a 5-year period in a large university medical center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…The method offered the possibility of performing acceptably good surveillance in areas where resources do not allow for traditional manual surveillance [76]. This hospital-wide approach generally results in lower sensitivities [4,13,63]. However, Tseng et al showed their hospital-wide EASS system performed very well in a 2,200-bed teaching hospital, with regard to sensitivity (0.98), specificity (0.99), positive predictive value (0.96), and negative predictive value (1) compared with their reference standard, which, remarkably, was a continuous manual, hospital-wide surveillance for BSI, including CLABSI, operating since 1981 [67].…”
Section: Bloodstream Infections (Including Central Line Associated)mentioning
confidence: 99%
“…The method offered the possibility of performing acceptably good surveillance in areas where resources do not allow for traditional manual surveillance [76]. This hospital-wide approach generally results in lower sensitivities [4,13,63]. However, Tseng et al showed their hospital-wide EASS system performed very well in a 2,200-bed teaching hospital, with regard to sensitivity (0.98), specificity (0.99), positive predictive value (0.96), and negative predictive value (1) compared with their reference standard, which, remarkably, was a continuous manual, hospital-wide surveillance for BSI, including CLABSI, operating since 1981 [67].…”
Section: Bloodstream Infections (Including Central Line Associated)mentioning
confidence: 99%
“…In total, 55 risk factors were identified across the three types of surgical procedures from literature [15], [18][19][20][21][22][23][24][25][26][27][28]. Of the risk factors identified, ASA class, body mass index (BMI), Preoperative length of stay and diabetes were identified as general risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…Weekly (alter two-weekly) prevalence surveys were performed during January 2013 until June 2014 using a semi-automated algorithm [21,22]. In short, an algorithm was used to calculate a nosocomial infection index (NII) which was then verified by infection control practitioners (ICP) in case of a positive outcome to determine whenever HAI was present or not.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21-23 However, current surveillance methods lack a systematic approach to detect changes or patterns in events that require acute interventions. Nor is surveillance currently used to predict antimicrobial resistance problems and upcoming outbreaks of diseases due to the lack of advanced analytics.…”
Section: Discussionmentioning
confidence: 99%